Visualization of the retina and vitreous during vitreoretinal surgery: new technologies. Issue 3 (May 2017) - Read, Sarah P.; Fortun, Jorge A.
Abstract : Purpose of review: Visualization remains a critical factor in successful ocular surgery. Here we review new technology that has the potential to allow for safer and more efficient retinal surgery. Recent findings: Vitreoretinal surgery poses unique visualization challenges such as the need for specialized optical systems and the delicate and microscopic features of retinal structures. Better retinal visualization allows for new approaches to increasingly complex retinal cases. Wide-angle viewing has allowed stereopic visualization of the peripheral retina. Improved lighting systems have shown better safety profiles and can facilitate bimanual techniques. The potential to improve surgical decision making has been shown with intraoperative imaging such as optical coherence tomography. Summary: Although some of the benefits of these developments have yet to be proven, improved technology for visualization during retinal surgery will hopefully allow for safer and more efficient surgeries.